2019
DOI: 10.1136/bmj.l4609
|View full text |Cite
|
Sign up to set email alerts
|

Clostridioides difficile: diagnosis and treatments

Abstract: Clostridioides difficile (formerly Clostridium) is a major cause of healthcare associated diarrhea, and is increasingly present in the community. Historically, C difficile infection was considered easy to diagnose and treat. Over the past two decades, however, diagnostic techniques have changed in line with a greater understanding of the physiopathology of C difficile infection and the use of new therapeutic molecules. The evolution of diagnosis showed there was an important under- and misdiagnosis of C diffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
86
0
28

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(114 citation statements)
references
References 187 publications
0
86
0
28
Order By: Relevance
“…As known to all, C. di cile and C. perfringens are highrisk infectious origins of AAD. The former can produce an enterotoxin (toxin A) and a cytotoxin (toxin B), which cause mucosal injury and colonic in ammation [7]. The later can produce potent protein toxins (αtoxin, β-toxin, ε-toxin, and -toxin), which cause many different histotoxic and enterotoxic diseases in humans and animals [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As known to all, C. di cile and C. perfringens are highrisk infectious origins of AAD. The former can produce an enterotoxin (toxin A) and a cytotoxin (toxin B), which cause mucosal injury and colonic in ammation [7]. The later can produce potent protein toxins (αtoxin, β-toxin, ε-toxin, and -toxin), which cause many different histotoxic and enterotoxic diseases in humans and animals [37].…”
Section: Discussionmentioning
confidence: 99%
“…We observed more serious diarrhea in mice which received cephradine + gentamycin sulfate than in mice which received lincomycin hydrochloride + ampicillin sodium and ceftriaxone sodium + erythromycin lactobionate [3]. Numerous studies reported that the mechanisms for AAD mainly laid on the changes or dysbiosis of microbial composition and function induced by antibiotics [4][5][6][7]. Although recent studies were concentrated on C. di cile-associated diarrhea, it accounts for only 10% -25% of all AAD cases [7].…”
Section: Introductionmentioning
confidence: 99%
“…We can distinguish three kinds of CDIs: (1) healthcare facility-onset (HO) CDI; (2) community-onset, healthcare facility-associated (CO-HCFA) CDI and (3) community-associated (CA) CDI. Although C. difficile was defined as the major cause of healthcare-associated diarrhoea in adult patients for decades [33], the rate of community-acquired CDI has increased [34]. Healthcare-associated infections remain the most frequent in adults, whereas community-associated CDI is 3-fold more common than healthcare-associated CDI in children.…”
Section: Classifications Of C Difficile Infection (Cdi) and Treatmenmentioning
confidence: 99%
“…In a recent review about CDI in adults, Benoit Guery et al reported on effects of probiotics, used concurrently with antibiotics, towards preventing C. difficile diarrhoea [33]. A randomized, double-blinded phase 3 trial showed that Lactobacillus spp.…”
Section: First Step: Conscientious Use Of Antibiotics and Role Of Promentioning
confidence: 99%
“…Stunden gekennzeichnet, die Infektion erfolgt im Rahmen einer "Lebensmittelvergiftung". Bei rezidivierenden Verläufen kann durch einen fäkalen Mikrobiota-Transfer (FMT, "Stuhltransplantation") sehr wirksam eine Heilung erreicht werden [6]. Andere neue Therapieansätze basieren auf der Gabe nichtresorbierbarer Betalaktamase, um die antibiotikabedingte Betalaktamasehemmung im Darm zu antagonisieren und der Entstehung einer Dysbiose vorzubeugen.…”
Section: Gemeldete Infektionen 100unclassified